CTCF-Induced Circular DNA Complexes Observed by Atomic Force Microscopy. Issue 6 (16th March 2018) - Mawhinney, Matthew T.; Liu, Runcong; Lu, Fang; Maksimoska, Jasna; Damico, Kevin; Marmorstein, Ronen; Lieberman, Paul M.; Urbanc, Brigita
Abstract: The CTCF protein has emerged as a key architectural protein involved in genome organization. Although hypothesized to initiate DNA looping, direct evidence of CTCF-induced DNA loop formation is still missing. Several studies have shown that the 11 zinc finger (11 ZF) domain of CTCF is actively involved in DNA binding. We here use atomic force microscopy to examine the effect of the 11 ZF domain comprising residues 266–579 (11 ZF CTCF) and the 3 ZF domain comprising residues 402–494 (6–8 ZF CTCF) of human CTCF on the DNA morphology. Our results show that both domains alter the DNA architecture from the relaxed morphology observed in control DNA samples to compact circular complexes, meshes, and networks, offering important insights into the multivalent character of the 11 ZF CTCF domain. Atomic force microscopy images reveal quasi-circular DNA/CTCF complexes, which are destabilized upon replacing the 11 ZF CTCF by the 6–8 ZF CTCF domain, highlighting the role of the 11 ZF motif in loop formation. Intriguingly, the formation of circular DNA/CTCF complexes is dominated by non-specific binding, whereby contour length and height profiles suggest a single DNA molecule twice wrapped around the protein. Graphical abstract: Highlights: CTCF-induced DNA morphologies are visualized by atomic force microscopy. DNA conformations induced by CTCF deviate from relaxed DNA conformations. CTCF induces formation of unique circular DNA/CTCF complexes. The 11 zinc finger motif of CTCF stabilizes circular DNA/CTCF complexes. Analysis of DNA/CTCF complexes suggests a DNA twice wrapped around CTCF.